Cruzipain and Its Physiological Inhibitor, Chagasin, as a DNA-Based Therapeutic Vaccine Against Trypanosoma cruzi - Cerny, Natacha (2020)
Chagas disease caused by the protozoan parasite Trypanosoma cruzi is endemic in 21 Latin American countries and the southern United States and now is spreading into several other countries due to migration. Despite the efforts to control the vector throughout the Americas, currently, there are almost seven million infected people worldwide, causing ~10,000 deaths per year, and 70 million people at risk to acquire the infection. Chagas disease treatment is restricted only to two parasiticidal drugs, benznidazole and nifurtimox, which are effective during the acute and early infections but have not been found to be as effective in chronic infection. No prophylactic or therapeutic vaccine for human use has been communicated at this moment. Here, we evaluate in a mouse model a therapeutic DNA vaccine combining Cruzipain (Cz), a T. cruzi cysteine protease that proved to be protective in several settings, and Chagasin (Chg), which is the natural Cz inhibitor. The DNAs of both antigens, as well as a plasmid encoding GM-CSF as adjuvant, were orally administrated and delivered by an attenuated Salmonella strain to treat mice during the acute phase of T. cruzi infection. The bicomponent vaccine based on Salmonella carrying Cz and Chg (SChg+SCz) was able to improve the protection obtained by each antigen as monocomponent therapeutic vaccine and significantly increased the titers of antigen- and parasite-specific antibodies. More importantly, the bicomponent vaccine triggered a robust cellular response with interferon gamma (IFN-γ) secretion that rapidly reduced the parasitemia during the acute phase and decreased the tissue damage in the chronic stage of the infection, suggesting it could be an effective tool to ameliorate the pathology associated to Chagas disease.